Neutralization of Omicron subvariants BA.1 and BA.5 by a booster dose of COVID-19 mRNA vaccine in a Japanese nursing home cohort. Issue 13 (24th March 2023) - Itamochi, Masae; Yazawa, Shunsuke; Inasaki, Noriko; Saga, Yumiko; Yamazaki, Emiko; Shimada, Takahisa; Tamura, Kosuke; Maenishi, Emi; Isobe, Junko; Nakamura, Masahiko; Takaoka, Misuzu; Sasajima, Hitoshi; et al.
Highlights: Receptor-binding domain IgG markedly increased after the 3rd dose of mRNA vaccine. Omicron neutralizing titer (NT) increased by the 3rd dose of mRNA vaccine. The decline in RBD IgG and NTs after the 3rd dose was age dependent. Breakthrough infection (BTI) occurred among the participants during study period. BTI induced a robust NT against BA.5 five month after the third dose. Abstract: The sustained epidemic of Omicron subvariants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a worldwide concern, and older adults are at high risk. We conducted a prospective cohort study to assess the immunogenicity of COVID-19 mRNA vaccines (BNT162b2 or mRNA-1273) in nursing home residents and staff between May 2021 and December 2022. A total of 335 SARS-CoV-2 naïve individuals, including 141 residents (median age: 88 years) and 194 staff (median age: 44 years) participated. Receptor-binding domain (RBD) and nucleocapsid (N) protein IgG and neutralizing titer (NT) against the Wuhan strain, Alpha and Delta variants, and Omicron BA.1 and BA.5 subvariants were measured in serum samples drawn from participants after the second and third doses of mRNA vaccine using SARS-CoV-2 pseudotyped virus. Breakthrough infection (BTI) was confirmed by a notification of COVID-19 or a positive anti-N IgG result in serum after mRNA vaccination. Fifty-one participants experienced SARS-CoV-2 BTI during the study period. The RBD IgG and NTs against Omicron BA.1 and BA.5 were markedly increased in SARS CoV-2 naïve participants 2 months after the third dose of mRNA vaccine, compared to those 5 months after the second dose, and declined 5 months after the third dose. The decline in RBD IgG and NT against Omicron BA.1 and BA.5 in SARS-CoV-2 naïve participants after the second and the third dose was particularly marked in those aged ≥ 80 years. BTIs during the BA.5 epidemic period, which occurred between 2 and 5 months after the third dose, induced a robust NT against BA.5 even five months after the booster dose vaccination. Further studies are required to assess the sustainability of NTs elicited by Omicron-containing bivalent mRNA booster vaccine in older adults.